Analysis of Cervical Cancer Tissue Using Raman Spectroscopy - Saputra, Rio; Suryatika, Ida Bagus Made; Wendri, Nyoman (BULETIN FISIKA; Vol 24 No 2 (2023): BULETIN FISIKA August EditionDO - 10.24843/BF.2023.V24.i02.p06, 2022)
Cervical cancer tissue analysis has been carried out using Raman Spectroscopy. The purpose of this study was to determine the effect of differences in power level and exposure time on the Raman spectrum pattern and to determine the power level and exposure time that can be used as a standard to distinguish normal and cancer cervical tissue spectrum patterns. This study used histological preparations of cancerous and normal cervical tissue. The preparations were made in the Anatomical Pathology Laboratory of Sanglah Hospital and the Bali Branch of the Indonesian Cancer Foundation. Samples were treated with power levels of 300 and 400 mW, with exposure times of 3000 and 4000 ms at a wavelength of 1064 nm. The resulting spectrum is then analyzed to be used as a standard in differentiating the spectrum pattern of normal and cancerous cervical tissue. Raman spectroscopy analysis with power levels of 300 and 400 mW on cervical tissue resulted in differences in intensity and shift in wave number. The maximum intensity difference is 0.211 au and the wavenumber shift is 7.257 cm -1 . Analysis of cervical tissue using Raman Spectroscopy with exposure times of 3000 and 4000 ms resulted in a difference in intensity of 0.022 au and a wave number of 1432.834 cm -1 . The scanning parameters that can be used as standards are 300 mW and 3000 ms with a maximum intensity of 760.392 and 1220.221 au at wave numbers of 1425.577 and 1432.834 cm -1 , respectively.